Cytomorphology of Chondroid Syringoma: Analysis of 20 Cases and Review of Literature - Agrawal, Meetu; Singh, Mukul; ., Rituraj; Kolte, Sachin; Ahluwalia, C; Madan, Neha; Aurora, Rasmi (Annals of Pathology and Laboratory Medicine, 2019)
Background: Chondroid syringomas [CS] are interesting skin adnexal tumours. They have a remarkable pleomorphic-adenoma like morphology in the skin. Though the histopathology of the tumour has been described in detail in literature, cytomorphological studies are restricted to case reports and small case series. For diagnosing a CS on cytology, the index of suspicion must be high, clinical evaluation must be thorough and knowledge of variant existing morphologies is essential. Aim: This study was done with the aim of studying the common and variant cytological features of chondroid syringomas. Methods: This was a retrospective study conducted over a four-year period (2014-17) in the Department of Pathology, VMMC and Safdarjung hospital. Fine needle aspirate smears and biopsy slides were studied. Morphological details were independently reviewed in detail by two pathologists (Dr MS and Dr MA). Result and Conclusion: The conventional biphasic cell morphology of CS was seen in nearly 50% cases. Rest of the cases showed predominance of one or more variant features in few areas and thus CS was only one of the differential diagnosis in these cases. Nevertheless, FNA proved to be fast, inexpensive and a reliable method for diagnosis of chondroid syringoma. The study will be relevant and helpful in the day to day cytological reporting of CS.